(untitled) (International journal of artificial intelligence, 2024)
English is a global language, often serving as a lingua franca. It is considered a "saviour" language because it can help you communicate in many foreign countries where person does not know the local language. The English language is considered to be a single entity but this language is spoken differently because of numerous dialects and accents. The reasons for these differences are social, historical, cultural and geographical factors. This article is aimed to illustrate different accents and dialects of English language.